Hepatocellular carcinoma presenting as a huge intra-abdominal mass: A case report - Okay, Erdem; Sarı, Alpaslan; Odabaşoğlu, Hülya; Uygun, Kazım; Sarısoy, Tahsin; Gürbüz, Yeşim (Turkish Journal of Gastroenterology, 2014)
Abstract Hepatocellular carcinoma (HCC) is the most common primary malignant tumor of the liver and is generally associated with hepatitis B or C virus-related cirrhosis. A giant intra-abdominal HCC mass that fills nearly the whole abdomen is not often reported in the literature. In this report, we present a case in which a patient with hepatitis B developed a giant intra-abdominal mass that originated from segment three of the liver and infiltrated the stomach and transverse colon. We were able to resect the tumor without leaving any tumor tissue behind. Although HCC presenting as a huge mass with invasion of the gastrointestinal tract is uncommon, this pathology should be considered in the differential diagnosis of giant intra-abdominal masses. The case presented here also indicates that surgical resection is possible in selected patients.